2006
DOI: 10.1158/0008-5472.can-06-1187
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin 1 Influences Colon Carcinoma Cell Migration by Cleavage of the Laminin-5 β3 Chain

Abstract: Matrilysin 1 [matrix metalloproteinase 7 (MMP7)] is one of the most important metalloproteinases expressed in human tissues. This enzyme is generally not expressed by normal differentiated epithelial colon cells, but has been shown to be up-regulated in human colon adenomas and adenocarcinomas. Little is known about the role of MMP7 in cell invasion and its involvement in proteolytic processes. By searching the ligands of MMP7 in the colonic carcinoma cells HT29, we identified laminin-5/laminin-332 (LN5) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 33 publications
4
59
0
Order By: Relevance
“…Migration of resident HSCs is believed to be critical for the progression of liver fibrosis because it accounts for the increased numbers of activated HSCs in areas of injury. 29 Moreover, MMP-7 is able to cleave ECM and basement membrane, 30 and mediate E-cadherin ectodomain shedding in injured lung epithelium, 24 leading to accelerated cell migration. In this study, the wound healing and Boyden chamber assays demonstrated that HSC-T6 cells expressing MMP-7(Asp-137) variant acquired an enhanced migratory capacity as compared with cells expressing MMP-7(Gly-137) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Migration of resident HSCs is believed to be critical for the progression of liver fibrosis because it accounts for the increased numbers of activated HSCs in areas of injury. 29 Moreover, MMP-7 is able to cleave ECM and basement membrane, 30 and mediate E-cadherin ectodomain shedding in injured lung epithelium, 24 leading to accelerated cell migration. In this study, the wound healing and Boyden chamber assays demonstrated that HSC-T6 cells expressing MMP-7(Asp-137) variant acquired an enhanced migratory capacity as compared with cells expressing MMP-7(Gly-137) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…48 Matrix metalloproteases (MMPs 7 and 20) have a central role in cell proliferation, migration, differentiation, angiogenesis, apoptosis and host defences and YAP1 is the critical downstream regulatory target in the Hippo signaling pathway, having a pivotal role in organ size control and tumor suppression by restricting proliferation and promoting apoptosis. 49,50 By contrast, the genes contained in the 13q32.1 HZD have not been yet associated with a role in cancer disease. The HZD located at 8p11.23-p11.22 and found in two MGUS patients is also of particular interest, as it contains only the ADAM3A gene, in which HZD has recently been reported in pediatric high-grade glioma and diffuse intrinsic pontine gliomas.…”
Section: %mentioning
confidence: 98%
“…During tissue remodeling, the γ2 subunit is further proteolyzed by MMP-2 to an 80 kD species [18]. The β3 laminin chain has also recently been found to be processed by the action of matrix metalloproteinase-7 (MMP-7, matrilysin-1) or membrane type1 (MT1)-MMP in several cell lines [19,20]. The proteolytic cleavage of the subunits of laminin-332 is biologically important and likely alters its interaction not only with cell-surface receptors but also with other ECM molecules [21].…”
Section: Subunits and Assembly Of Matrix Adhesive Complexesmentioning
confidence: 99%
“…MMP-3, MMP-12, MMP-13, MMP-19, and MMP-20 have also been reported to cleave the γ2 laminin subunit, and enhance epithelial cell migration [80,81]. With regard to the laminin β3 chain, MMP-7 (matrilysin) cleaves the laminin β3 chain into a 90-kD subunit at Ala(515)-Ile(516) [19,82]. This 90-kD product has been reported to stimulate the migration of colon carcinoma cells [19].…”
Section: Relation To Cancermentioning
confidence: 99%
See 1 more Smart Citation